Mitos Wanita Pada Desain Kemasan Sabun Pembersih Kewanitaan - Monica Revias Purwa Kusuma; Aji Susanto Anom Purnomo (LP2M Sekolah Tinggi Seni Rupa dan Desain Visi Indonesia (STSRD VISI), 2020)
A wider market in which there are various kinds of products makescompetition fierce for the attention of consumers. In plain view,many similar items have almost similar visual elements, one of whichis feminine cleaning products. The feminine sanitizer packagingbottle has a distinctive curve and is almost similar from one brand toanother. This study aims to examine a work of VisualCommunication Design in the form of packaging design of femininecleansing soap products. The feminine cleansing soap productssampled were Herborist, Resik V, and Sumber Ayu, and all threecontain the same content, namely betel leaf extract. The researchmethod used in this research is descriptive qualitative with the theoryof the meaning of connotations and myths of Roland Barthes. Theresults of the analysis of connotative and mythological meanings ofthe three samples of feminine cleansing soap show that there aresimilarities in the meanings of verbal and visual signs. Theseproducts carry the same image which is constructed through theconnotations and myths of the hope of every woman to have afragrant, clean, healthy, healthy area of womanhood and does notinterfere with daily activities. Meanwhile, the meaning of myth in thepackaging design of feminine cleansing soap reveals that the shapeof the packaging design bottle is an ideal image of a woman's body.